Phenotyping the physiological and biochemical changes of nopal cladodes during early postharvest storage - Valenzuela-García, Jesús Rodolfo; Luna-Maldonado, Alejandro Isabel; Méndez-Dorado, Mario Alberto; Cadena-Zapata, Martín; Arredondo-Valdez, Juan; Valenzuela Carrizales, Mónica Gabriela; López López, Juan Antonio; de la Peña-Casas, Blanca Elizabeth; López-López, Gilbert Fresh; Buendía-García, Alain; Gómez-Leyva, Juan Florencio (Frontiers in Plant Science, 2026)
This study assessed short-term postharvest changes in morphological, colorimetric, and biochemical traits of Opuntia ficus-indica (nopal) cladodes across four commercial categories (Cambray, C, B, and A) over 10 days, with measurements at 3, 6, and 9 days. Parameters included weight, size, texture, thickness (base, center, tip), color (hue angle, chroma), chlorophyll a, b, total, pheophytins, antioxidant capacity (ABTS, DPPH, FRAP), and total phenolic and flavonoid contents. ANOVA and Tukey’s HSD tests were applied. Size, chroma, and hue angle did not vary significantly across categories. Thickness remained stable for categories C and B; Cambray varied at base, center, and tip; A varied at base and tip. Weight changed in Cambray and A but remained constant in C and B. Firmness differences were observed in Cambray and B, but not in C and A. Category B had the highest chlorophyll a (412 mg/100 g DW), chlorophyll b (327 mg/100 g DW), total chlorophyll (739 mg/100 g DW), and pheophytins (9229.2 mg/100 g DW). Ascorbic acid was highest in A (7.81 mg/g). ABTS values were highest in C (3.51 mmol TE/100 g DW) and A (3.43 mmol TE/100 g DW), while DPPH (0.63 mmol TE/100 g DW) and FRAP (1.70 mmol TE/100 g DW) peaked in C. Polyphenols were highest in Cambray (103.8 GAE/100 g DW) and C (99.2 GAE/100 g DW), and flavonoids were highest in A (280.5 mg QE/100 g DW). The optimal category showed stable size, firmness, thickness, and color, alongside the highest chlorophyll and pheophytin contents. These findings reveal postharvest dynamics and biochemical diversity in nopal, providing valuable insights for agricultural management and industrial applications.